2014
DOI: 10.1002/rcs.1585
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted level II-IV neck dissection through a modified facelift incision: initial North American experience

Abstract: Robot-assisted selective neck dissection of levels II-IV is feasible through a modified facelift incision. Our initial data suggest that this procedure is surgically sound. It should be applied by experienced surgeons who wish to avoid a cervical incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…The gasless unilateral axillary approach, gasless unilateral axillo‐breast approach, bilateral axillo‐breast approach, and combined transaxillary and retroauricular approach were designated together as the transaxillary technique. The retroauricular, postauricular, and modified facelift approaches comprised the retroauricular technique …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gasless unilateral axillary approach, gasless unilateral axillo‐breast approach, bilateral axillo‐breast approach, and combined transaxillary and retroauricular approach were designated together as the transaxillary technique. The retroauricular, postauricular, and modified facelift approaches comprised the retroauricular technique …”
Section: Methodsmentioning
confidence: 99%
“…Following this, Kim et al combined the facelift and transaxillary approach to perform neck dissections in head and neck squamous cell carcinoma. Multiple case series and comparative studies, primarily out of South Korea, subsequently highlighted the feasibility of nodal dissection through robotic transaxillary, retroauricular, and modified facelift approaches . Despite the embrace of this technology in East Asia, studies remain limited in the head and neck surgical literature.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 We devised procedures for robot-assisted neck dissection (RAND) of regional nodal metastases in head and neck cancers that are slowly gaining in popularity among head and neck surgeons regardless of patient's ethnicities. [3][4][5][6][7] However, the timeline ref-…”
mentioning
confidence: 97%
“…Therefore, to overcome the limitations mentioned above, robot-assisted radical or selective neck dissections via a retroauricular approach or a modified face-lift approach have been reported. 97, 98, 99, 100, 101, 102, 103, 104, 105, 106 The results suggested that the robot-assisted surgery lasted longer than conventional surgery, but the intraoperative bleeding, lymph node retrieval, volume of drainage, hospitalization and related complications of robot-assisted neck dissection (RAND) were similar to those of open neck dissection. Furthermore, the patients who underwent robotic surgery were much more satisfied with the postsurgical aesthetics than those who underwent open surgery.…”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%